2018
DOI: 10.1007/s00167-018-4882-x
|View full text |Cite
|
Sign up to set email alerts
|

No evidence for the most appropriate postoperative rehabilitation protocol following anterior cruciate ligament reconstruction with concomitant articular cartilage lesions: a systematic review

Abstract: IV.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
16
0
2

Year Published

2018
2018
2021
2021

Publication Types

Select...
6
4

Relationship

0
10

Authors

Journals

citations
Cited by 23 publications
(18 citation statements)
references
References 43 publications
0
16
0
2
Order By: Relevance
“…There is a lack of literature to guide this decision as evidenced by a recent systematic review that failed to find a consensus on postoperative rehabilitation and RTS for concomitant ACL reconstruction and articular cartilage lesions. 67 However, meniscal and cartilage injuries were reported to be associated with lower rates of RTS. 32 In addition, after revision ACL reconstruction, significant chondral damage was associated with lower RTS rates.…”
Section: Consensus Statements and Discussionmentioning
confidence: 99%
“…There is a lack of literature to guide this decision as evidenced by a recent systematic review that failed to find a consensus on postoperative rehabilitation and RTS for concomitant ACL reconstruction and articular cartilage lesions. 67 However, meniscal and cartilage injuries were reported to be associated with lower rates of RTS. 32 In addition, after revision ACL reconstruction, significant chondral damage was associated with lower RTS rates.…”
Section: Consensus Statements and Discussionmentioning
confidence: 99%
“…Clinicians follow specific stepwise progression rehabilitation criteria and rely on several clinical and impairment-based criteria before allowing patients to return to sports 7 8 11–13. There is substantial heterogeneity in the ACL rehabilitation protocols available online14 and in the scientific literature 15–19. Criteria for when to let the athletes progress are not standardised and experts disagree on the choice of follow-up patient-reported and physical performance-based outcome measures 19 20.…”
Section: Introductionmentioning
confidence: 99%
“…Failla et al 17,18 found superior functional outcomes and higher RTS rates among athletes who participated in extended preoperative rehabilitation including neuromuscular training compared with those who did not. Although a 2018 systematic review determined there is no evidence to support a single, most appropriate rehabilitation protocol after ACLR, 48 clinical practice guidelines 31,32 exist, and several criterion-based postoperative rehabilitation protocols 1,11,28,35,50 have been proposed. Two recent articles provide high-quality evidence supporting the use of such criterion-based approaches to achieve objective criteria, including ≥90% strength and hop test limb symmetry indexes, prior to RTS.…”
mentioning
confidence: 99%